Hospital pharmacy - Hassan, William E. (Philadelphia, Pennsylvania : Lea & Febiger, 1986)
Since the publication of the first edition of hospital pharmacy in 1965, the institutional practice of pharmacy has made great progress. Professional hospital and clinical pharmacists now practice in hospitals, extended care facilities, nursing homes, neighborhood health centers and satellite clinics.
1. Introduction -- 2. The hospital and its organization -- 3. The pharmacy-its organization -- 4. The pharmacy and therapeutics committee -- 5. The hospital formulary -- 6. Pharmacy communications -- 7. Investigational use drugs -- 8. Developing the budget -- 9. Purchasing and inventory control -- 10. Medical service representative-pharmacist -- 11. The pharmacy procedural manual -- 12. Policy and procedure for drug distribution and administration -- 13. Dispensing to in-patients -- 14. Dispensing to ambulatory patients -- 15. Distributing ancillary supplies -- 16. Dispensing of controlled substances -- 17. Tax-free alcohol-its procurement and control -- 18. Dispensing during off-hours -- 19. Hospital reimbursement -- 20. Prepacking in the hospital -- 21. Manufacturing-bulk and sterile -- 22. The pharmacy-central sterile supply room -- 23. The nuclear pharmacy -- 24. The physical plant and its equipment -- 25. The pharmacy library-drug information center -- 26. The role of the hospital pharmacist in educational and training programs -- 27. Preparation of the annual report -- 28. Safe Use of medications in the hospital -- 29. The small hospital, nursing homes, hospices, and part-time pharmacists -- 30. Computers in the hospital pharmacy.
Includes index.
Keywords: HOSPITAL PHARMACIES